Clinical and pathological findings in three dogs with a corneocentric presentation of nodular granulomatous episcleritis. (6th February 2019) - Hamzianpour, Negar; Heinrich, Christine; Jones, R. Gareth; McElroy, Peter; Wilson, Neil; Scurrell, Emma
Abstract: Purpose: To describe the clinical signs, management, histopathologic findings, and outcome of three dogs with a corneocentric presentation of nodular granulomatous episcleritis (NGE). Methods: Three dogs of varying breeds were presented for a unilateral, nonpainful, and infiltrative corneal lesion in the dorsal aspect of the eye. Clinical response to symptomatic topical treatment directed at a presumed inflammatory or immune‐mediated cause was poor. Due to this, and concerns of neoplasia, ultrasonography (n = 1), incisional biopsy (n = 2), and/or enucleation (n = 2) were performed. Results: The inflammatory infiltrate observed on histopathology was identical to that seen in nodular granulomatous episcleritis in all three cases. However, atypically the inflammation was confined to the cornea and limbus, without episcleral or conjunctival involvement. Inflammation of the cornea was full thickness to Descemet's membrane. Following enucleation (n = 2), there were no postoperative complications, and no reported ophthalmic disease in the remaining eye. Currently, the single non‐enucleated case remains controlled with systemic and topical immunosuppression. Conclusion: To the best of the authors' knowledge, this is the first report of an NGE condition purely affecting the full thickness of the cornea, without episcleral or conjunctival involvement. The authors propose this to represent an atypical corneocentric variant of NGE. This clinical presentation can resemble neoplasia; incisional biopsy is recommended for a definitive diagnosis. Further research into the optimal treatment strategies for this variant of NGE is required.